Transcatheter interventions for left-sided valvular heart disease complicated by cardiogenic shock - Fraccaro, Chiara (2023)
Valvular heart disease (VHD) is one of the most frequent causes of heart failure (HF) and is associated with poor prognosis, particularly among patients with conservative management. The development and improvement of catheter-based VHD interventions have broadened the indications for transcatheter valve interventions from inoperable/high-risk patients to younger/lower-risk patients. Cardiogenic shock (CS) associated with severe VHD is a clinical condition with a very high risk of mortality for which surgical treatment is often deemed a prohibitive risk. Transcatheter valve interventions might be a promising alternative in this setting given that they are less invasive. However, supportive scientific evidence is scarce and often limited to small case series. Current guidelines on VHD do not contain specific recommendations on how to manage patients with both VHD and CS. The purpose of this clinical consensus statement, developed by a group of international experts invited by the European Association of Percutaneous Cardiovascular Interventions (EAPCI) Scientific Documents and Initiatives Committee, is to perform a review of the available scientific evidence on the management of CS associated with left-sided VHD and to provide a rationale and practical approach for the application of transcatheter valve interventions in this specific clinical setting.